Computation of total hemispherical emissivty from directional spectral models. (June 2017) - King, Jonathan L.; Jo, Hangjin; Loyalka, Sudarshan K.; Tompson, Robert V.; Sridharan, Kumar
Highlights: A GOA model to predict spectral directional emissivity of metal surfaces. Total hemispherical emissivity obtained via spectral directional model sampling. Components of roughness, wavelength, and others accounted for during calculations. Approach is benchmarked against a variety of experimental data. Abstract: Kirchoff's law and experimentally obtained data and/or theory (such as from Drude's model) for optical constants have been used in a modified geometric optics approximation (GOA) to obtain directional spectral emissivity. Then this spectral emissivity is used to obtain the total hemispherical emissivity by integration over direction and spectral range as weighted by the Planck distribution. The computations account for surface dependencies on temperature, composition, and roughness. The computed results for both the spectral directional and the total hemispherical emissivity are compared with the available data for platinum, stainless steel 304, and tungsten surfaces.